Modulation of the Photophysical Properties of Pyrene by the Microstructures of Five Poly(alkyl methacrylate)s Over a Broad Temperature Range - Atvars, Teresa D. Z. (2013)
Pyrene fluorescence spectra have been recorded in five poly(alkyl methacrylate)s (where alkyl is ethyl butyl, isobutyl, cyclohexyl and hexadecyl) over a 20–400 K temperature range. The changes in the position and the full width at half maximum (FWHM) of the 0–0 emission band (peak I) have been correlated with the structural characteristics of the alkyl groups in the different relaxation regimes of the polymers to assess the degree of coupling of the excited singlet states with the polymer cybotactic regions. Data treatment of the peak I positions using an electron–phonon model indicates that longitudinal optical modes are involved, and that the magnitude of coupling depends on the polymer structure and follows the same trend as the glass transition temperatures. The same spectral parameters have been correlated also with “hole” free volumes from positron annihilation spectroscopy over temperature ranges which span the glass or melting transitions of the polymers. Reasons why free volume and FWHM measurements follow the same trends, and other aspects of the systems, are discussed.